The Association between Single Nucleotide Polymorphisms rs1042522 and rs1642785 in the TP53 gene and Acute Myeloid leukemia in a sample of the Baghdad/ Iraq population (Baghdad Science Journal, 2024)
Acute myeloid leukemia (AML) represents the most prevalent type of acute leukemia in adults and is responsible for approximately 80% of all cases. The tumor suppressor gene (TP53) is a gene that has been frequently studied in cancer, and mutations in this gene account for about 50% of human cancers. This study aims to evaluate the correlation between two single nucleotide polymorphisms (SNPs) in the gene: rs1042522 and rs1642785, and a group of Iraqi patients suffering from pre-diagnostic acute myeloid leukemia (AML). Blood samples were collected from sixty patients (26 males and 34 females) and sixty controls (26 males and 34 females); these subjects were matched in gender, age, and ethnicity. Genomic DNA has been extracted from whole frozen blood samples by using the Easy Pure® Blood Genomic Kit, and then the purity and concentration have been measured by using the Nano drop NAS-99 spectrophotometer. Nano Drop readings ranged between 7-55ng/µl for the concentration and between 1.78-1.9 for the purity. High resolution melt (HRM) real-time PCR was used in the detection of these two SNPs. TP53 genotype frequencies have been in accordance with Hardy–Weinberg equilibrium (HWE), with statistically significant differences p≤0.05 between the genotypes of the control and patient groups. The rs1042522 genotype frequency was significantly different between patients and controls p = 0.0001, and participants with the GA genotype were more likely to develop AML OR = 7.8, 95% CI 3.2–18.4, p= 0.0001. In addition, the genotype frequency of rs1642785 was significantly different between patients and controls p = 0.002, and participants with the GA genotype were more likely to develop AML OR = 3.5, 95% CI 1.5–8.12, p = 0.002.